1999
DOI: 10.1111/j.1574-6941.1999.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transgenic T4-lysozyme-producing potato plants on potentially beneficial plant-associated bacteria

Abstract: A field release of genetically engineered potato plants that produce bacteriophage T4‐lysozyme for enhanced bacterial resistance was monitored for changes in plant‐associated bacterial populations, in the functions of potentially beneficial bacteria and in the diversity of antagonistic bacterial species. These parameters have been analyzed for two T4‐lysozyme‐expressing lines, a transgenic control and a non‐transgenic line, over a period of 2 years at different stages of plant development and at two different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 36 publications
6
52
0
1
Order By: Relevance
“…However, in both microenvironments (rhizosphere and geocaulosphere) no statistically significant Fig. 2 Selective enrichments of antagonistic populations in the rhizosphere according to results obtained in a six-year field trial with Verticillium host plants (Berg et al , 2005 differences between transgenic and non transgenic plants were found in the following parameters: (i) the abundances of bacteria, (ii) the percentage of auxinproducing bacteria, (iii) the percentage of antagonistic bacteria, and (iv) on the diversity of bacterial antagonists on genotypic and phenotypic level (Lottmann and Berg 2001;Lottmann et al 1999;Lottmann et al 2000). In an additional approach, rifampicin resistant mutants of two antagonistic plant-associated bacteria were used for seed tuber inoculation of transgenic and nontransgenic potato lines.…”
Section: Plant Specificity Of Microbial Communities In the Rhizosphermentioning
confidence: 98%
“…However, in both microenvironments (rhizosphere and geocaulosphere) no statistically significant Fig. 2 Selective enrichments of antagonistic populations in the rhizosphere according to results obtained in a six-year field trial with Verticillium host plants (Berg et al , 2005 differences between transgenic and non transgenic plants were found in the following parameters: (i) the abundances of bacteria, (ii) the percentage of auxinproducing bacteria, (iii) the percentage of antagonistic bacteria, and (iv) on the diversity of bacterial antagonists on genotypic and phenotypic level (Lottmann and Berg 2001;Lottmann et al 1999;Lottmann et al 2000). In an additional approach, rifampicin resistant mutants of two antagonistic plant-associated bacteria were used for seed tuber inoculation of transgenic and nontransgenic potato lines.…”
Section: Plant Specificity Of Microbial Communities In the Rhizosphermentioning
confidence: 98%
“…Die Applikation Rifampicin-resistenter Spontanmutanten der Biokontrollstämme zählt zu den gän-gigsten Methoden, um die Populationsdynamik inokulierter Stämme zu beobachten (Lottmann et al 1999;Viebahn et al 2005). Durch die Entwicklung einer entsprechend spezifischen Realtime-PCR kann die Populationsdynamik der applizierten BCA-Stämme noch exakter und auch unabhängig von der Verfügbarkeit Antibiotika-resistenter Mutanten untersucht werden.…”
Section: Sscp-analyseunclassified
“…These interactions may be very sensitive to fluctuations in environmental factors, like the presence of specific microorganisms (Andreote et al 2004) or the cultivation of different species of plants (Salles et al 2004). In this scenario, the possibility that genetic modification of plants causes shifts in the microbial communities should be considered (Lottmann et al 1999;Heuer and Smalla 1999;Schmalenberger and Tebbe 2002;Gyamfi et al 2002;Baumgarte and Tebbe 2005). Hence, microbial communities could be used as indicators of environmental impact caused by the transgenic plants cultivation.…”
Section: Introductionmentioning
confidence: 98%